2009
DOI: 10.1039/b913415h
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of persistent organic pollutants in Africa. Part 1: Passive air sampling across the continent in 2008

Abstract: A 6-month air sampling survey was conducted at 26 sites across the African continent with the aim to establish baseline information on contamination of ambient air with persistent organic pollutants (POPs) as a reference for future monitoring programs in the region. Sampling sites included continental, rural and urban backgrounds, agricultural and industrial sites as well as waste and obsolete pesticide dumps. Concentrations of polycyclic aromatic hydrocarbons, polychlorinated dibenzo-p-dioxins and furans, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 6 publications
(7 reference statements)
4
35
0
Order By: Relevance
“…Surprisingly, a study by Klanova et al . [] using passive samplers found that the PAH concentrations at a background site in Mauritius (latitude −20.23, longitude 57.49), located to the east of Madagascar, were significantly higher than those of samples from Zimbabwe and South Africa. Although the PAH concentrations based on the passive samplers only represent the gaseous PAHs, both gas and particle phase PAHs could change similarly with the change of the emission sources [ Akyüz and Çabuk , ].…”
Section: Resultsmentioning
confidence: 97%
“…Surprisingly, a study by Klanova et al . [] using passive samplers found that the PAH concentrations at a background site in Mauritius (latitude −20.23, longitude 57.49), located to the east of Madagascar, were significantly higher than those of samples from Zimbabwe and South Africa. Although the PAH concentrations based on the passive samplers only represent the gaseous PAHs, both gas and particle phase PAHs could change similarly with the change of the emission sources [ Akyüz and Çabuk , ].…”
Section: Resultsmentioning
confidence: 97%
“…POPs in air have been monitored in central and northern Europe, central parts of North America, as well as in the Arctic (e.g., Holoubek et al 2007;Hung et al 2010). Other understudied regions have recently been studied using passive air sampling, which comes with a factor of ≈2 uncertainty (e.g., Pozo et al 2009Pozo et al , 2012Klánová et al 2009;Halse et al 2011), and also in Turkey (no results published; MoEU 2015). In some parts of the world, including Turkey, our knowledge of POP levels is very sparse and mainly relies on campaign-based (short-term) observations (Lohmann et al 2007;Klánová et al 2011).…”
Section: Responsible Editor: Constantini Samaramentioning
confidence: 99%
“…As the insect menace and mosquito breeding are high during monsoon season, the obtained results clearly indicate the proportional usage of DDT to control mosquitoes, etc. The global production of DDT during 2005 was 6,269 metric tons (Klanova et al 2009), but in India, through National Vector Borne Disease Control Program, 4,930 metric tons of DDT was provided to states during 2008 for vector control (Toxic Links Fact Sheet 2011).…”
Section: Diagnostic Ratio Of Ddts and Hchsmentioning
confidence: 99%